Magnetic resonance imaging findings of infectious sacroiliitis associated with iliopsoas abscess: a case report in a young male - D. Diacinti; C. Gioia; F. Vullo; G. Cannavale; C. Catalano; G. Valesini (PAGEPress Publications, 2018)
Infectious sacroiliitis is an infection of the sacroiliac joint, not easy to diagnose because of its non-specific signs, symptoms and laboratory abnormalities. We describe a case of a 16 year-old male with 5 days' history of fever, abdominal pain, constipation, low-back and left hip pain extended to the left knee associated with sudden inability to walk. In the first place, magnetic resonance imaging (MRI) examination of his sacroiliac joint revealed an enlarged corpuscolated fluid collection near the left iliopsoas muscle, extended to homolateral paravertebral muscles and a little fluid at the left sacroiliac joint. Drainage by aspiration of the iliopsoas abscess was applied; Staphylococcus aureus was found in the aspirated fluid and isolated from the blood too. Therefore intravenous antibiotic therapy was begun. Follow-up MRI exams confirmed the muscle abscess and revealed also a spongy bone edema of the left sacroiliac joint, persisting despite the disappearance of symptoms and the normalization of inflammatory values. It is important to make an early diagnosis of infectious sacroiliitis in order to begin antibiotic therapy as soon as possible, because of the increasing morbidity of infection of sacroiliac joint. In our case MR findings have provided significant orientation towards the final diagnosis of infectious sacroiliitis.